The knight's bride prize - Matthews, Ella (Harlequin historicals., 2024)
A dramatic medieval convenient-marriage story Will he risk his mission For her hand in marriage? On a secret quest to expose a traitor, Sir Hugh enlists in a tournament to win the hand of his target's daughter, Lady Bronwen. But the clever, driven maiden jeopardizes his plans when their unexpected attraction threatens to distract him from his duty! She's desperate to escape her father, and Hugh can protect her by claiming his prize and marrying her. Yet honor demands the noble knight keep their desire at bay, for completing his mission means betraying his new bride's trust.